Maize growth in Aluminum-rich Vertisoils from the lowland pre-Amazonia, Baixada Maranhense, Brazil - Costa-da Silva, Alessandro (Agronomía Mesoamericana, 2014)
The present work studied the influence of Aluminm (Al3+) in the growth of maize plants grown in soil samples collected from a lowland region of Brazil in which tillage is practiced. The effect of Al3+ on maize roots and the amount of dry matter produced (root, leaf and stem) was measured. The chemical characterization was also performed in the Ap horizon of four soils samples from the lowland region known as Baixada Maranhense (pre-Amazonia, Brasil): Santa Rita (SR), Arari (AR) and Vitoria do Mearim (VM), all Vertisoils; and 1 Oxisoil (T) from the municipality of São Luís, Área del Núcleo de Tecnología Rural (T), which was used as a control group. The study was performed in 2009 in a greenhouse using 2 dm3 of soil per pot. Also, the samples were divided into samples with and without fertilization. Variation in root length and dry matter of leaves differed significantly between samples treated with and without fertilizer, except in the control locality T. The production of dry matter of root, stem and leaf was higher in all soils when fertilized. The control soil also outperformed all others in terms of dry matter production in the root, possibly resulting in a lower amount of Al3+ (1.2 cmolc/dm3) compared with SR, AR and VM soils (6, 8, 8.0 and 7.0 cmolc/dm3 respectively). Results suggest fertilization reduces the detrimental effect of aluminum in maize production in the Baixada Maranhense.